2010
DOI: 10.1021/es903636c
|View full text |Cite
|
Sign up to set email alerts
|

U(VI) Reduction to Mononuclear U(IV) by Desulfitobacterium Species

Abstract: The bioreduction of U(VI) to U(IV) affects uranium mobility and fate in contaminated subsurface environments and is best understood in Gram-negative model organisms such as Geobacter and Shewanella spp. This study demonstrates that U(VI) reduction is a common trait of Gram-positive Desulfitobacterium spp. Five different Desulfitobacterium isolates reduced 100 microM U(VI) to U(IV) in <10 days, whereas U(VI) remained soluble in abiotic and heat-killed controls. U(VI) reduction in live cultures was confirmed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 44 publications
12
141
0
Order By: Relevance
“…The P coordination and the generalized periplasmic mineralization observed in the PilA − mutant cells suggest that U(VI) permeated deep and fast into the cell envelope, where it formed carboxyl and phosphoryl-coordinated complexes with periplasmic proteins and the peptidoglycan layer (30,31) and membrane phospholipids (33), respectively. The formation of a mononuclear U(IV) phase has also been reported for other bacteria of relevance to U bioremediation (34,35), yet contrasts with earlier reports of uraninite formation by Geobacter spp. (10,36).…”
Section: Discussion Physiological Relevance Of the Extracellular Redumentioning
confidence: 67%
See 1 more Smart Citation
“…The P coordination and the generalized periplasmic mineralization observed in the PilA − mutant cells suggest that U(VI) permeated deep and fast into the cell envelope, where it formed carboxyl and phosphoryl-coordinated complexes with periplasmic proteins and the peptidoglycan layer (30,31) and membrane phospholipids (33), respectively. The formation of a mononuclear U(IV) phase has also been reported for other bacteria of relevance to U bioremediation (34,35), yet contrasts with earlier reports of uraninite formation by Geobacter spp. (10,36).…”
Section: Discussion Physiological Relevance Of the Extracellular Redumentioning
confidence: 67%
“…(10,36). The chemical composition of the medium can influence the nature of the reduced U mineral (34). We used a bicarbonate buffer and conditions used in previous studies with G. sulfurreducens (13), whereas studies reporting uraninite formation used PIPES-buffered solutions (36) or bicarbonatebuffered uncontaminated groundwater (10).…”
Section: Discussion Physiological Relevance Of the Extracellular Redumentioning
confidence: 99%
“…Although bacteria can enzymatically reduce uranium, abiotic processes leading to uranium reduction in the environment are also likely to be important. While studies have considered uraninite to be the primary product of uranium reduction (Langmuir 1978), evidence from this and other (Fletcher et al, 2010;Bernier-Latmani et al, 2010) work strongly suggests the formation of non-uraninite species of reduced uranium including monomeric U(IV) species. Importantly, the presence of structural or sorbed phosphate inhibits uraninite formation.…”
Section: Conclusion and Environmental Implicationsmentioning
confidence: 76%
“…Finally, batch uranium reduction experiments with Gram positive, spore-forming bacteria Desulfotomaculum reducens MI-1 and Clostridium acetobutylicum as well as the Gram negative bacterium S. oneidensis MR-1 carrying the reduction in a similar medium as the Gram positive bacteria resulted in the formation of monomeric U(IV) (Bernier-Latmani et al, 2010). Likewise, Fletcher et al (2010) reported formation of mononuclear U(IV) by Desulfitobacterium spp.…”
Section: Discussionmentioning
confidence: 89%
“…Bernier-Latmani et al, 2010;Fletcher et al, 2010;Veeramani et al, 2011;Sharp et al, 2011;Cologgi et al, 2011). The species may form along with the crystalline U(IV) phase uraninite, UO 2 (s), in laboratory experiments and in field-scale remediation efforts that aim to reduce U(VI) to less soluble U(IV) species.…”
Section: Introductionmentioning
confidence: 99%